Quantitative Evaluation of Vocabulary Emotional Color in Language Teaching - Zhong Caihong (Occupational Therapy International)
Objective. In real communication, the context is complex and changeable and the color and meaning of some words will wander in the context. The development and changes of words are more complex and multidimensional than before. Compared with the rational meaning of words, the color meaning of words can better reflect the psychological mode and way of thinking of the Han nationality but it is difficult for foreign learners to accurately grasp and misunderstandings often occur. In order to solve this problem, it is necessary to summarize and explain the words whose color meanings are easily shifted, so as to help the students accurately grasp the color meanings of the words and better help Chinese learners to realize the communicative function of the language. Method. This paper takes the scope of emotional words as the starting point and proposes that emotional words are words with emotional colors. The four aspects of whether words belong to emotional words define the concept of emotional words and introduce the specific methods of judging and extracting emotional words from the two aspects of dictionary definition and word collocation. This paper takes foreign students whose native language is English as the research object, through questionnaire survey and corpus analysis, to investigate the use of foreign students’ emotional colors and to explore the influence of native language factors on emotional color acquisition. Based on the research of modern Chinese ontology and the existing research results in the field of teaching Chinese as a foreign language, this paper takes the theory of interlanguage and transfer theory as the theoretical basis and mainly uses the methods of comparative analysis and error analysis to try to find out the relationship between emotional color teaching and acquisition. Results/Discussion. The basic pattern and quantity distribution of lexical emotion correction for beginners, intermediate, and advanced learners of Chinese as a second language were analyzed, and the restrictive factors and characteristics were explained. Similarities and differences and the rationale behind them were explored. In the process of international Chinese teaching, teachers mostly pay attention to the rational meaning of words, while ignoring the teaching of the emotional meaning of words. The lack of vocabulary emotion and meaning teaching is prone to errors in students’ understanding and use. With the increase of the vocabulary of intermediate and advanced learners, many words with similar colors and meanings appear, which brings a lot of difficulties for students to distinguish between synonyms. If the use of words with emotional meanings is not accurate, it is easy to cause communication barriers.